Analisis Profil Pelajar Pancasila pada Tokoh Sejarah K.H. Ahmad Dahlan - Merci Robbi Kurniawanti; Lisa Rukmana (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The Pancasila Student Profile cannot be realized instantly, but requires habituation. One of the efforts that can be made to realize this is by emulating historical figures who can be used as role models. As it is known that today's young generation, especially students are experiencing an exemplary crisis. One historical figure who can be used as an example by the younger generation in order to strengthen the profile of Pancasila students is K.H Ahmad Dahlan. This study uses a qualitative method with a literature study which aims to explore character values in the character K.H Ahmad Dahlan that are relevant to the profile of Pancasila students. The findings of this study are that in K.H Ahmad Dahlan there are six character values that are relevant to the profile of Pancasila students, namely: 1) faith, fear of God Almighty and noble character, 2) global diversity, 3) mutual cooperation, 4 ) independent, 5) critical reasoning, and 6) creative. These six values are reflected in the ideas and actions taken by K.H Ahmad Dahlan.